Standardization of Marking of the Surgical Borders According to the Fibonacci (Golden) Ratio in Female Genital Aesthetic Surgery: Presentation of a Novel Marking Gadget - Erhan Okuyan; Emre Gunakan; Nurullah Peker (IMR Press, 2024)
The anatomy of the female external genitalia may differ due to developmental or acquired events. However, several anatomical landmarks such as the anterior and posterior commissures, glans clitoridis, and perineal body do not differ across most patients and can be used to evaluate post-surgical tissue symmetry and proportion. Patient preference seems to be subjective; interestingly, however, the desired post-surgical appearance is very similar in itself, almost to the standard in most patients. In addition, surgeons may change the entire process according to their individual aesthetic perceptions and experience. Thus, the outcomes of genital aesthetic surgery may be affected by multiple factors, with patient preference and surgical evaluation and approach appearing to be the most person-dependent. From this perspective, we defined a sticker model for marking the external female genitalia in genital aesthetic surgery. Inspired by the golden ratio, we incorporated the Fibonacci spiral in the stickers.